Efektivitas Metode Pembelajaran Berbasis Teknologi Chromebook Dalam Pembelajaran Agama Islam Di SDN 74 Bolang - Taufik Taufik; Hamran Hamran; Syamsuriah Syamsuriah; Amaluddin Amaluddin (Journal of Humanities, Social Sciences, and Education, 2025)
This study aims to analyze the effectiveness of using Chromebooks in Islamic Religious Education (ISE) learning in elementary schools by emphasizing changes in student motivation, participation, and understanding during the learning process. The study used descriptive qualitative methods through observation, interviews, and documentation involving teachers and fifth-grade students. The results showed that Chromebooks helped increase student engagement through more visual, interactive, and accessible presentations of material. Teachers found it easier to deliver material and conduct evaluations through digital applications such as Google Classroom and Google Forms. Students also demonstrated increased learning motivation because they could access videos, images, and interactive exercises that made ISE materials more engaging. However, this study also found that the use of digital devices requires adequate infrastructure support for optimal learning. Teachers need to continuously develop digital literacy competencies, while students require mentoring to ensure they are able to utilize learning features effectively. By meeting these needs, technology integration is expected to continuously improve the quality of learning in elementary schools. This demonstrates the importance of collaboration between schools, teachers, and parents in supporting innovation-based learning.